Efficacy of progestin-primed ovarian stimulation in women with polycystic ovary syndrome undergoing in vitro fertilization: a systematic review and meta-analysis - Yang, Liu; Liang, Fuxiang; Yuan, Yue; Luo, Xufei; Wang, Qi; Yao, Liang; Zhang, Xuehong (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is a common endocrinopathy causing infertility in childbearing women. Progestin-primed ovarian stimulation (PPOS) protocol has recently been used for infertile women. However, whether PPOS provides a significant benefit over gonadotropin-releasing hormone (GnRH) analogue protocols in PCOS is still controversial. The objective of this systematic review is to investigate the efficacy of PPOS in patients with PCOS during in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). We searched Medline, Embase, Google Scholar, ClinicalTrials, and Cochrane Central Register of Controlled Trials from inception to April 1, 2023. Randomized controlled trials (RCTs) and observational studies comparing the efficacy between PPOS and conventional GnRH analogue protocols in patients with PCOS in English were included. The primary outcomes included live birth rate, the incidence of moderate or severe ovarian hyperstimulation syndrome (OHSS), and the number of metaphase II oocytes. The pooled estimates were calculated using the random-effects models as odds ratios (OR) or mean differences (MD) with 95% confidence intervals (CIs). Three RCTs and six cohort studies involving 2289 patients were included. Results from RCTs suggest that PPOS leads to no significant difference in the risk of OHSS, the number of metaphase II oocytes, or the rate of live birth when compared to GnRH analogue protocols. The pooling estimates of cohort studies showed consistent results. Additionally, in cohort studies, PPOS required a higher dose of Gn and tended to improve the implantation rate, clinical pregnancy rate, and ongoing pregnancy rate. For subgroup analyses, the higher implantation rate, clinical pregnancy rate, and ongoing pregnancy rate were found in PPOS compared to the GnRH agonist short protocol. However, the certainty of the evidence for the outcomes was generally low. Overall, There is currently no evidence to support that PPOS could reduce the risk of OHSS, increase oocyte maturation, or improve pregnancy outcomes in women with PCOS undergoing IVF/ICSI when compared to GnRH analogue protocols. Considering its efficiency and safety, this protocol could be a patient-friendly and viable alternative for PCOS patients, especially when frozen-thawed embryo transfer is planned. Future high-quality randomized trials with children’s long-term safety and cost-effective analyses are still required. System Review Registration NPLASY (202340059). https://inplasy.com/inplasy-2023-4-0059/